Prospects for the Development of SAIC Motor Corporation Limited in the Russian Market - Kaiyang Li; Anna Korenevskaya (Communications of International Proceedings, 2022)
The growth of the Chinese economy is an example of increasing the competitiveness of the country, especially in the last 20 years. Until recently, most of this growth was accounted for by the production of labor-intensive goods with low added value. However, today China's economy is no longer limited to the production of low-level products. The Chinese government has clearly defined a goal for domestic manufacturers regarding international market capture. One of the world's largest car manufacturers, SAIC Motor Corporation Limited, is analyzed in this paper. A growth matrix was built, a SWOT analysis and a PEST analysis were carried out, and an optimal possible strategy for the company's behavior in the Russian market was proposed as part of the study.
Keywords: SAIC Motor Corporation Limited; SAIC; SAIC Motor; Strategic Analysis; Success Factors; Profit Potential; Growth Strategy; Automotive